The Fortification of the Strait of Magellan: Project for the Image of the Monarchy - Zuleta Carrandi, Joaquín (Revista Complutense de Historia de América, 2013)
These pages are dedicated to providing a description of the fortification project for the Strait of Magellan (1581), considering new sources and offering a critique of the traditional ones. The context analyzed is the process of transformation of the fortification project as a result of its debate in Spain. I maintain that it ought to be interpreted as part of the propagandistic apparatus of the Spanish Monarchy.